The relationship between teachers’ pre service training and teachers’ performance / Nur Fathiah Omar, Rohaida Abdul Kelam and Syarifah Munyati Syed Ab Rahman - Mohammad, Ashuhada; Alias, Munirah; Ali, Siti Abidah (2012)
Teachers’ pre service training is the training provided by government to the perspectives teachers so that they can learn about the skills and knowledge about teaching from professional educators, then they can practice it in actual classroom teaching and learning process. The variables chose to describe the relationship of teachers’ pre service training and their performance is relate to the purpose of attending pre service training before being able to teach in class. This study sought to identify the relationship between teaching methodology learn during pre service training, the student needs of the teachers’ per service training, teachers’ training and their management of classroom, teaching strategies learn at pre service training that can be apply in teaching process, how to relate pre service training with developing student interest and the importance and effect of this variables towards teachers’ performance. To assess the relationship between teachers’ pre service training, the researchers studied respondents in SMK Sultan Omar, Dungun. Respondents being provided with questionnaires which require them to answer it, then result from the questionnaire was used to analyze the data. The study revealed that the teachers who answered the questionnaires basically agree with the question asked.